Robust Optimization of Hosting Capacity of Distributed Photovoltaics in Distribution Network Considering Adjustable Characteristics of 5G Base Station - Tong SUN; Shenxi ZHANG; Yi CAO; Jiachen CAO; Haozhong CHENG (Zhongguo dianli, 2025)
With distributed photovoltaics access massively, which is characterized by stochasticity and volatility, has posed new technical challenges to the safe and reliable operation of the distribution network. To evaluate and improve the hosting capacity of distributed photovoltaics in distribution network, the article proposed a robust optimization method for the hosting capacity of distributed photovoltaics in the distribution network, which considers adjustable characteristics of 5G base stations. Firstly, a 5G base station adjustable characteristics model is constructed, which considers the communication load migration and the dynamic power backup of the energy storage. Secondly, a robust optimization model of the maximum hosting capacity of distributed photovoltaics in the distribution network with 5G base stations is established. Then, the model is solved using an increasingly tight linear cut algorithm combined with a column-and-constraint generation algorithm. Finally, the effectiveness of the model is verified on an improved IEEE 33-node distribution network, and the effects of source-load uncertainty, 5G base station communication load migration, and dynamic energy storage backup on the maximum access capacity of distributed photovoltaics in distribution network are analyzed.